2018
DOI: 10.1111/dom.13505
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights from sequential combination therapy with a sodium glucose co‐transporter‐2 inhibitor and a dipeptidyl peptidase‐4 inhibitor: Results from the CANARIS Trial using canagliflozin and teneligliptin

Abstract: The result suggested that the dominant mechanism responsible for the glucose metabolism reflected in the G/I ratio was attributable to SGLT2i and that its active mechanism persisted, despite adding a DPP-4i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The efficacy of the empagliflozin ? linagliptin FDC was also evaluated in drug-naı ¨ve patients [46][47][48][49][50] Certain anecdotal studies have been conducted in Japan on the effect of sequential therapy with a combination of canagliflozin and teneligliptin in patients with T2DM [46,47]. However, since the FDC has not been approved in major markets like the USA, Europe, and India, the evidence from these studies is beyond the scope of this review.…”
Section: Efficacy Of Sglt2i 1 Dpp4i Fdcsmentioning
confidence: 99%
“…The efficacy of the empagliflozin ? linagliptin FDC was also evaluated in drug-naı ¨ve patients [46][47][48][49][50] Certain anecdotal studies have been conducted in Japan on the effect of sequential therapy with a combination of canagliflozin and teneligliptin in patients with T2DM [46,47]. However, since the FDC has not been approved in major markets like the USA, Europe, and India, the evidence from these studies is beyond the scope of this review.…”
Section: Efficacy Of Sglt2i 1 Dpp4i Fdcsmentioning
confidence: 99%
“…Okahata et al reported that canagliflozin and canagliflozin/teneligliptin combination therapy improved blood glucose levels after MTT in 26 participants in a hospitalized setting for 6 days [19]. This study presented that canagliflozin increased that serum glucagon level during MTT and addition of teneligliptin reversed this increase.…”
Section: Discussionmentioning
confidence: 57%
“…It has also been reported that glucagon secretion from alpha cells, in which no SGLT2 is expressed, of the pancreatic islets are suppressed via the SGLT1 inhibition effect [25]. However, some studies have reported increased glucagon levels with canagliflozin [26], further examination of There is a possibility that the metabolic cascade initiated from the energy deprivation followed by inhibiting renal reabsorption of glucose by SGLT2i extends to central nervous system (CNS) like "entero-insular-central axis", but no clinical data in this trial could elucidate this hypothesis, although ipragliflozin made some influence on leptin, which is known concerned with CNS [27].…”
Section: Discussionmentioning
confidence: 99%